Auditoría del rubro compras - cuentas por pagar de una empresa dedicada a la publicidad al aire libre por el período terminado al 31 de diciembre del 2008 - Paredes Maruri, Lourdes Marisol (2010)
This work consisted of conducting the financial audit to the payable account – shopping item of a company dedicated t outdoor advertising. The development target of this paper is to show through and analytical and determining review the Company´s financial statements, a criterion on of the reasonableness of the accounts and compliance with generally accepted accounting principles. For this, one proceeded to perform the respective analysis of the risk of fraud and obtaining the risk matrix, the same that influence on the development of the audit plan. There was realized the calculation the matter according to what is provided according ISA 240, analytical procedures and preliminary analysis of the internal control component of the company, to then, define our audit strategy, which is based on controls moderate trusts. Finally, it developed substantive tests of the items mentioned above.